A forest of history: the Maya after the emergence of divine kingship - Stanton, Travis W., editor; Brown, M. Kathryn, editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2020)
Essays that critically engage with and build upon previous contributions made to Maya epigraphy, iconography, material culture, and history. Cutting-edge research on the social changes leading up to the spread of divine kinship across the lowlands in the first part of the Early Classic.--Provided by publisher.
See the forest for the trees: an introduction to the volume / Travis W. Stanton and M. Kathryn Brown -- "Terminal" termination rituals and the felling of A forest of kings: past struggles and recent triumphs of the core concepts of a seminal work / Arthur A. Demarest -- The materialization of Classic period Maya warfare: Caracol stranger-kings at Tikal / Arlen F. Chase and Diane Z. Chase -- Maya usurpers / Joyce Marcus -- Forest of queens: the legacy of royal Calakmul women at El Perú-Waka's central civic-ceremonial temple / Olivia C. Navarro-Farr, Griselda Pérez Robles, Damaris Menéndez, and Juan Carlos Pérez Calderón -- Statecraft in the City of the Centipede: burials 39, 38, and internal alliance building at El Perú-Waka', Guatemala / Michelle Rich and Keith Eppich -- Revisiting Bird Jaguar and the Sajal of the Yaxchilán Kingdom / Charles W. Golden and Andrew K. Scherer -- Macaw Mountain and ancient peoples of Southeast Mesoamerica / Wendy Ashmore -- Borderland politics: a reconsideration of the role of Yaxuná in regional Maya politics in the latter part of the Classic / Travis W. Stanton, Aline Magnoni, Stanley P. Guenter, José Osorio León, and Francisco Pérez Ruíz -- In search of paradise: religion and cultural exchange in Early Postclassic Mesoamerica / Karl A. Taube -- Empire at Chichén Itzá revisited / Annabeth Headrick -- Closing the portal at Itzmal Ch'en: effigy censers and termination rituals at a Mayapán ceremonial group / Marilyn A. Masson, Wilberth Cruz Alvarado, Carlos Peraza Lope, and Susan Milbrath -- On Copán Stela 11 and the origins of the ill omen of Katun 8 Ahau / Stanley P. Guenter -- Into the woods: archaeology, epigraphy, and iconography in Classic Maya studies / David A. Freidel.
Keywords: Schele, Linda -- Forest of kings; Mayas -- Kings and rulers; Mayas -- History; Mayas -- Antiquities; Indians of Central America -- Antiquities; Tikal Site (Guatemala) -- Antiquities; Caracol Site (Belize) -- Antiquities; Calakmul Site (Mexico)